Depression among patients with tuberculosis: determinants, course and impact on pathways to care and treatment outcomes in a primary care setting in southern Ethiopia—a study protocol. Issue 7 (8th July 2015) - Ambaw, Fentie; Mayston, Rosie; Hanlon, Charlotte; Alem, Atalay
Abstract : Introduction: Depression is commonly comorbid with chronic physical illnesses and is associated with a range of adverse clinical outcomes. Currently, the literature on the role of depression in determining the course and outcome of tuberculosis (TB) is very limited. Aim: Our aim is to examine the relationship between depression and TB among people newly diagnosed and accessing care for TB in a rural Ethiopian setting. Our objectives are to investigate: the prevalence and determinants of probable depression, the role of depression in influencing pathways to treatment of TB, the incidence of depression during treatment, the impact of anti-TB treatment on the prognosis of depression and the impact of depression on the outcomes of TB treatment. Methods and analysis: We will use a prospective cohort design. 703 newly diagnosed cases of TB (469 without depression and 234 with depression) will be consecutively recruited from primary care health centres. Data collection will take place at baseline, 2 and 6 months after treatment initiation. The primary exposure variable is probable depression measured using the Patient Health Questionnaire-9. Outcome variables include: pathways to treatment, classical outcomes for anti-TB treatment quality of life and disability. Descriptive statistics, logistic regression and multilevel mixed-effect analysis will be used to test the study hypotheses. Ethics and dissemination: Ethical approval has been obtained from the Institutional Review Board (IRB) of the College of Health Sciences, Addis Ababa University. Findings will be disseminated through scientific publications, conference presentations, community meetings and policy briefs. Anticipated impact: Findings will contribute to a sparse evidence base on comorbidity of depression and TB. We hope the dissemination of findings will raise awareness of comorbidity among clinicians and service providers, and contribute to ongoing debates regarding the delivery of mental healthcare in primary care in Ethiopia.